Analogue Controlled Active Power Filter for Pulsating Loads - Edberg, Fredrik; Skoog, Axel (My University, 2026)
This master thesis demonstrates an analogue controlled active power filtration for pulsing load used in radar systems. The main tasks of this thesis was to simulate, design, build and verify a regulation control system on a printed circuit board. This regulation card was connected with a separate power card and should be able to handle 40A pulsed loads without any critical drop in output voltage. The active power filter together with the control card was simulated in LTspice before component selection and a schematic and a layout was designed in KiCad. Then the active power filter with the regulation control system was constructed and verified to make sure it works as intended. The active power filter managed to maintain the output voltage during pulses within a certain limit, dropping to 27.1V, resulting in a viable solution for handling pulsating loads. However, the duty cycle specified of 10% had to be reduced to 9.1% in order to maintain steady state operation due to high transient currents up to 150A during 40A pulses. Improvements, such as a less aggressive control loop and dynamic limits, needs to be implemented to achieve stable operation at higher duty cycle.
Keywords: APF, Pulsed loads, Control, Regulation, PCB, filter, power, design